Quantifying conjugation rates in clinical and environmental matrices: a systematic review to inform risk assessment - Quon, Hunter; Ramirez, Lucia; Bagwell, Blakeley; Moralez, Jennifer; Sheppard, Richard J.; Lopatkin, Allison J.; Hamilton, Kerry A. (Frontiers in Microbiomes, 2025)
IntroductionAntimicrobial resistance (AMR) has become a major public health concern and challenge. The transfer of antimicrobial resistance genes (ARG) between bacteria and the movement of antibiotic resistant bacteria (ARB) between human, environmental, and animal reservoirs allows AMR to spread and drive its persistence. Modeling efforts are useful for providing understanding of fate and transport, dynamics, or probabilistic risk, but lack estimates of bacterial conjugation parameters to be used within these frameworks.MethodsA systematic literature review was conducted to summarize measured rates of conjugation for AMR and other resistances across a variety of settings, experimental media, and donor sources. Results: Across the 113 studies, reported conjugation frequencies and rates were examined in environmental, clinical, and animal/agricultural settings. The findings spanned over 12 orders of magnitude. From all studies, a subset of 25 were able to be analyzed for time-dependent rate estimation, which is most useful in modeling approaches. The highest rates were found in samples originating from wastewater sources or transferred in wastewater matrices, pointing to the significance and role of anthropogenic impacts on the environment in dissemination of AMR.DiscussionThe results allowed us to identify knowledge gaps in measuring conjugation rates in key environmental exposure areas, such as biofilms, and in reporting experimental outputs for understanding cell growth and conjugation dynamics, such as donor, recipient and transconjugant densities over time.